Educational Function of the State as an Object of Administrative and Legal Regulation - V. V. Abroskin (Law and Safety)
The emphasis has been placed on the fact that the state has the main responsibility for the formation of state policy in the field of education and the development of effective mechanism for its implementation. The author has emphasized that without the development of effective mechanism for the implementation of the educational function of the state it will be impossible to ensure the proper functioning of all spheres of public life: political, economic, cultural, environmental, informational, law enforcement, etc. In this regard, it has been focused on the importance of clarifying the content of the educational function of the state, developing effective mechanisms for its implementation.